2014
DOI: 10.1186/1757-1146-7-24
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of a multi‐segment foot model with a 15‐marker set in healthy adults

Abstract: BackgroundSeveral 3D multi-segment foot models (MFMs) have been introduced for the in vivo analysis of dynamic foot kinematics. However, reproducibility of a model should be checked and ascertained before clinical utilization of a MFM. The purpose of this study was to determine the reliability of recently introduced MFM with a 15-marker set by assessing the participant’s stride-to-stride (intra-session) and visit-to-revisit (inter-session) repeatability.MethodsTwenty healthy adults with a mean age of 28.9 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…In our previous study, we confirmed that a MFM with a 15 marker set, which was proposed by Henley et al [15], showed a comparable intra-session and inter-session repeatability with other MFMs [16]. Also we showed that intersegmental angular measurements using this model was correlated with static radiographic measurements [17].…”
Section: Introductionsupporting
confidence: 86%
“…In our previous study, we confirmed that a MFM with a 15 marker set, which was proposed by Henley et al [15], showed a comparable intra-session and inter-session repeatability with other MFMs [16]. Also we showed that intersegmental angular measurements using this model was correlated with static radiographic measurements [17].…”
Section: Introductionsupporting
confidence: 86%
“…A 12‐camera system (VICON MOTION SYSTEM®, Oxford Metrics, UK; camera resolution 4 Mega Pixels, capturing frequency 200 Hz) in combination with three strain‐gauge force plates (Advanced Mechanical Technology, Inc.) was used to trace spherical markers. The extended Cleveland Clinical Marker Set was used as a kinematic model . A regression equation was used to define the hip joint center .…”
Section: Methodsmentioning
confidence: 99%
“…15,28 In brief, placement of the markers was as follows: 2 markers were placed on the knee (knee lateral and knee medial), 3 markers on the tibial shank (shank upper, shank front, and shank rear), 2 on the ankle (ankle lateral and ankle medial), 2 on the hindfoot segment (heel and distal), 2 on the midfoot segment (navicular and cuboid), 3 on the forefoot segment (MTH1, toe, MTH5), and 1 on the hallux (hallux; Figure 4). 28 They defined this foot model to consist of the hindfoot, forefoot, first lay, fifth ray, and hallux. The relationships between segments were calculated in sagittal, coronal, and axial planes from a ZXY Euler decomposition of the relative orientation of the anatomical coordinate systems.…”
Section: Intersegmental Angle Measurements During Gait Using a Multismentioning
confidence: 99%